Hubungan Penggunaan Kontrasepsi Hormonal Terhadap Kejadian Hipertensi pada Wanita Usia Subur di BPM Fitria Ningsih Siadari Kab. Karawang Jawa Barat - Fitria Ningsih Siadari; Adelina Sembiring; Lisbet Gurning (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Hypertension is a major risk factor for cardiovascular disease and contributes significantly to global morbidity and mortality. In Indonesia, the prevalence of hypertension in Women of Reproductive Age (WUS) reaches around 28.2%, while the use of hormonal contraception—especially injections, pills, and implants—is still a popular choice among couples of reproductive age. Several studies have shown a relationship between the use of exogenous hormones and increased blood pressure, but specific data at the local service facility level are still limited. This study aims to determine the relationship between the use of hormonal contraception and the incidence of hypertension in WUS at BPM Fitria Ningsih Siadari, Karawang Regency, West Java. This study used a cross-sectional analytic design. A sample of 102 WUS (15–49 years) who actively visit BPM Fitria Ningsih Siadari will be taken using purposive sampling. The independent variables include the type of hormonal contraception and duration of use; the dependent variable is hypertension status (blood pressure ≥ 140/90 mm Hg). Demographic data and confounding factors (age, BMI, family history of hypertension, salt intake, physical activity) were collected through questionnaires and standard blood pressure measurements. Bivariate (Chi square) and multivariate (logistic regression) analyses were used to evaluate the association, with a significance level of p <0.05. The results obtained The use of hormonal contraception in BPM Fitria Ningsih Siadari, Karawang Regency, West Java in 2023, the majority used injectable contraception, as many as 58 respondents (56.9%). Blood pressure in BPM Fitria Ningsih Siadari, Karawang Regency, West Java in 2023 was mostly grade 1 hypertension, as many as 46 respondents (45%). There was a relationship between the use of hormonal contraception and the incidence of hypertension in women of childbearing age (WUS) in BPM Fitria Ningsih Siadari, Karawang Regency, West Java in 2023 with a p value = 0.000